New and Not So New Lawn Grasses for Florida - Laurie E. Trenholm; J. Bryan Unruh (EDIS)
ENH 1033, a 7-page illustrated fact sheet by L.E. Trenholm and J.B. Unruh, looks at some of the lawn grasses that have been around in Florida for a long time, as well as some of the newer releases. Published by the UF Department of Environmental Horticulture, April 2006.